Seasonal variations in the distribution of aliphatic hydrocarbons in surface sediments from the Selangor River, Peninsular Malaysia's West Coast - Magam S.M.; Masood N.; Alkhadher S.A.A.; Alanazi T.Y.A.; Zakaria M.P.; Sidek L.M.; Suratman S.; Alrabie N.A. (Springer, 2025)
The seasonal variation of petroleum pollution including n-alkanes in surface sediments of the Selangor River in Malaysia during all four climatic seasons was investigated using GC?MS. The concentrations of n-alkanes in the sediment samples did not significantly correlate with TOC (r = 0.34, p > 0.05). The concentrations of the 29 n-alkanes in the Selangor River ranged from 967 to 3711 g g-1dw, with higher concentrations detected during the dry season. The overall mean per cent of grain-sized particles in the Selangor River was 85.9 2.85% sand, 13.5 2.8% clay, and 0.59 0.34% gravel, respectively. n-alkanes are derived from a variety of sources, including fresh oil, terrestrial plants, and heavy/degraded oil in estuaries. The results of this study highlight concerns and serve as a warning that hydrocarbon contamination is affecting human health. As a result, constant monitoring and assessment of aliphatic hydrocarbons in coastal and riverine environments are needed. ? 2023, The Author(s), under exclusive licence to Springer Nature B.V.